2017
DOI: 10.1111/ddi.12552
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation and modification of the ballast water microbial community during voyages into the Canadian Arctic

Abstract: Johansson, M. L.; Chaganti, S. R.; Simard, N.; Howland, K.; Winkler, G.; Rochon, A.; Laget, F.; Tremblay, P.; Heath, Daniel D.; and MacIsaac, Hugh J., "Attenuation and modification of the ballast water microbial community during voyages into the Canadian Arctic" (2017). Diversity and Distributions, 23, 5,[567][568][569][570][571][572][573][574][575][576] 36Results Ion Torrent sequencing returned approximately 2.9 million reads and revealed 37 significant monthly differences in diversity and species richness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
(67 reference statements)
0
6
0
Order By: Relevance
“…While that study did not investigate changes in taxonomic diversity, a number of other studies employing morphological analysis of both phyto- and zooplankton have described dramatic declines in both abundance and richness during the course of individual voyages of varying lengths ( Gollasch et al, 2000a ; Gollasch et al, 2000b ; Olenin et al, 2000 ). Using molecular approaches, Johansson et al (2017) similarly found that overall taxonomic richness of microbial communities assessed by 16S sequencing declined significantly over time during three separate transits of the Canadian arctic. Another HTS-based examination of metazoan diversity across 39 BW samples also found significant negative correlation of BW age with molecular diversity ( Rey et al, 2019 ).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…While that study did not investigate changes in taxonomic diversity, a number of other studies employing morphological analysis of both phyto- and zooplankton have described dramatic declines in both abundance and richness during the course of individual voyages of varying lengths ( Gollasch et al, 2000a ; Gollasch et al, 2000b ; Olenin et al, 2000 ). Using molecular approaches, Johansson et al (2017) similarly found that overall taxonomic richness of microbial communities assessed by 16S sequencing declined significantly over time during three separate transits of the Canadian arctic. Another HTS-based examination of metazoan diversity across 39 BW samples also found significant negative correlation of BW age with molecular diversity ( Rey et al, 2019 ).…”
Section: Discussionmentioning
confidence: 91%
“…Assessments of bacterial and fungal communities, which have traditionally posed extreme challenges for conventional assessments, have benefited especially from these emerging tools ( Hess-Erga et al, 2019 ). Recent studies have investigated diversity of bacterial communities across multiple samples entering ports both in the US ( Brinkmeyer, 2016 ; Lymperopoulou and Dobbs, 2017 ) and internationally ( Gerhard and Gunsch, 2019a ; Johansson et al, 2017 ), while others have explored fungal ( Gerhard and Gunsch, 2019b ) and protistan diversity ( Pagenkopp Lohan et al, 2016 ; Pagenkopp Lohan et al, 2017 ; Wu et al, 2017 ), including focal species with potential for negative human health impacts. Metabarcoding has also been employed to explore the impacts of BW treatments such as electrochlorination, UV exposure, and alkalinity on bacterial communities ( Fujimoto et al, 2014 ; Petersen et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, while barcoding databases are increasing very rapidly (Briski, Ghabooli, Bailey, & MacIsaac, ), substantial variation in coverage of different taxonomic groups hinders matching to field‐based sequences. Nevertheless, high‐resolution DNA metabarcoding‐based approaches are an important step toward improving the resolution and efficacy of NIS surveillance and risk assessment (Darling & Frederick, ; Johansson et al, ; Rey et al, ; Zaiko et al, ). We advocate that combing DNA with RNA analysis, which is capable of differentiating living and dead portions of communities, will improve DNA metabarcoding‐based tools for NIS risk assessment and management.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a growing interest in applying metabarcoding, the simultaneous identification of taxa present in a complex environmental sample, for BW monitoring so that the limitations of morphological taxonomy can be circumvented. , Most of the studies performed so far have relied on bulk samples (e.g., plankton net samples) , and on DNA extracted from filtered water to target micro-organismal communities. , Over the last years it has been recognized that macro-organisms can also be retrieved from filtered water through the recovery of traces of DNA released in the environment in the form of cells, feces, skin, saliva, mucus, etc., the so-called environmental DNA (eDNA). Yet, although eDNA is burgeoning as a cost-effective method to uncover macro-organismal diversity, to our knowledge, only a few studies have explored its potential for BW monitoring targeting macro-organisms. , Additionally, the effect of BW sampling access location (i.e., the location the tank is accessed to collect a sample, e.g., manhole or sounding pipe) on the eDNA-derived biodiversity estimates, recognized as one major factor impacting BW communities, has not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%
“…10,19−26 Most of the studies performed so far have relied on bulk samples (e.g., plankton net samples) 10,26 extracted from filtered water to target micro-organismal communities. [19][20][21][22][23][24][25]27 Over the last years it has been recognized that macro-organisms can also be retrieved from filtered water through the recovery of traces of DNA released in the environment in the form of cells, feces, skin, saliva, mucus, etc., 28 the so-called environmental DNA (eDNA). Yet, although eDNA is burgeoning as a cost-effective method to uncover macro-organismal diversity, to our knowledge, only a few studies have explored its potential for BW monitoring targeting macro-organisms.…”
Section: ■ Introductionmentioning
confidence: 99%